2001
DOI: 10.1007/s00244-002-1116-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metals on Seed Germination, Root Elongation, and Coleoptile and Hypocotyl Growth in Triticum aestivum and Cucumis sativus

Abstract: A simple, fast, and easy-to-perform method was carried out for the quantification of the inhibitory effects of metals on wheat and cucumber. The method uses seed germination, root elongation, and hypocotyl and coleoptile growth in these plants as parameters in the presence of varying concentrations of metals. Metals selected for this study were Hg, Cd, Co, Cu, Pb, and Zn. Although effective concentrations of these metals for a certain degree of inhibition were different, both plants had a reduced seed germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
165
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(198 citation statements)
references
References 20 publications
12
165
2
7
Order By: Relevance
“…At high concentrations, the metal is capable of causing the death of the seed embryos because oxidative stress is generated and important cellular components are damaged. At lower concentrations, mercury can alter the pattern of hydration and germination of the seeds (Munzuroglu & Geckil 2002;Jain et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At high concentrations, the metal is capable of causing the death of the seed embryos because oxidative stress is generated and important cellular components are damaged. At lower concentrations, mercury can alter the pattern of hydration and germination of the seeds (Munzuroglu & Geckil 2002;Jain et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals can affect plant physiology in different phases of a plant's development (Munzuroglu & Geckil 2002), and mercury has various effects on seed homeostasis. In P. reticulata, the dose dependent application of this metal is capable of altering the hydration process of the seeds and causing the death of the embryo.…”
Section: Discussionmentioning
confidence: 99%
“…Seeds inoculated in solidified MS medium without any suspension of MNPs were taken as control. Seed germination is extensively used in phytotoxicity test because it is simple, low cost and most suitable for unstable samples or chemicals (Munzuroglu and Geckil 2002;Wang et al 2001). Maximum germination frequency was observed in seeds treated with AgNPs suspensions, while minimum seed germination was seen in seeds treated with AuNPs.…”
Section: Effect Of Mnps Suspension On Seed Germinationmentioning
confidence: 99%
“…Peralta et al (2001) showed that Cr, Cu, Cd, Ni, and Zn ions reduce the germination rate of the Medicago sativa L. seeds as well as the size of the radicles and tigellas of the resulted seedlings. Munzuroglu and Geckil (2002) studied the influence of metal ions such as Hg 2+ , Cd 2+ , Co 2+ , Cu 2+ , Pb 2+ and Zn 2+ on the germination of Triticum aestivum and Cucumis sativum seeds and highlighted the inhibition of this process depending on the concentration and the reduction of the length of both radicle, hypocotyls and coleoptile of the seedlings. In contrast with our observations, the experiments carried out by Huţanu et al (2013) in the concentration range from 10 -4 M to 10 -2 M DNP demonstrated the strong toxicity of 3×10 -3 M concentration of 2,4-dinitrophenol on the wheat seeds.…”
Section: Discussionmentioning
confidence: 99%